ANALYSIS OF THE IMPLEMENTATION OF ACCOUNTING PRACTICES AND UNDERSTANDING OF VILLAGE FUND ALLOCATION AT BUMDES "MULTI GUNA" SIDOMULYO VILLAGE, MADIUN REGENCY - Ayu Rahmawati, Labbaika Dwi; Tiaramurti, Galuh; Nugrahaningsih, Putri; Arista, Denty; Saputro, Zaim Arif Eko (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
The application of accounting is one of the important factors in preparing financial reports. Financial reports are prepared based on applicable financial accounting standards with the aim of providing convenience in decision making, such as in the BUMDes Multi Guna Desa Sidomulyo where the application of accounting in presenting financial reports is very important, but in its presentation it still does not present cash flow reports and notes to financial reports this is due to (1) Understanding the Application of Accounting in presenting Financial Reports that are not in accordance with applicable standards, (2) Village funds are allocated based on priorities set by the village government, but transparency and accountability in the allocation process are still limited (3) Human Resources (HR) are inadequate. This study aims to determine the obstacles in the application of accounting & management of village fund allocations at BUMDes Multi Guna Desa Sidomulyo. The research method used is a descriptive method, namely describing, describing, and comparing data. Data collection techniques are qualitative through secondary and primary data. After the data is collected, an analysis is carried out using SWOT. The results of this study indicate that the understanding and education factors that are the background for the application of accounting and the allocation of village funds are not correct and appropriate